Petty Crimes and Their Incorporation into Misdemeanour Law: A Comparative Perspective and de Lege Ferenda Considerations - Tičar, Bojan; Pastirk, Gal (11. Nacionalna konferenca o varnosti v lokalnih skupnostih: Odpornost lokalnih skupnosti na varnostna tveganja, 2025)
The criminal law treatment of petty offences, such as minor theft and fraud, in the Slovenian legal system places a disproportionate burden on criminal justice authorities and often fails to ensure effective sanctioning. This article analyses the existing de lege lata framework, examining whether certain acts currently classified as criminal offences could be more appropriately addressed under misdemeanour law as a more suitable legal response. The core of the paper presents a comparative analysis of regulation in three European Union Member States – the Czech Republic, Slovakia and Poland – where the boundary between criminal offences and misdemeanours is drawn differently. These approaches provide grounds for considering possible changes to Slovenian legislation. The article concludes with de lege ferenda orientations, particularly regarding the introduction of more balanced and sustainable solutions within the misdemeanour system, while ensuring adequate protection of public order and fundamental rights.